Interspecific genetic differences and historical demography in South American arowanas (Osteoglossiformes, Osteoglossidae, Osteoglossum) - Souza, Fernando Henrique Santos de (Genes, 2020)
The South American arowanas (Osteoglossiformes, Osteoglossidae, Osteoglossum) are emblematic species widely distributed in the Amazon and surrounding basins. Arowana species are under strong anthropogenic pressure as they are extensively exploited for ornamental and food purposes. Until now, limited genetic and cytogenetic information has been available, with only a few studies reporting to their genetic diversity and population structure. In the present study, cytogenetic and DArTseq-derived single nucleotide polymorphism (SNP) data were used to investigate the genetic diversity of the two Osteoglossum species, the silver arowana O. bicirrhosum, and the black arowana O. ferreirai. Both species differ in their 2n (with 2n = 54 and 56 for O. ferreirai and O. bicirrhosum, respectively) and in the composition and distribution of their repetitive DNA content, consistent with their taxonomic status as different species. Our genetic dataset was coupled with contemporary and paleogeographic niche modeling, to develop concurrent demographic models that were tested against each other with a deep learning approach in O. bicirrhosum. Our genetic results reveal that O. bicirrhosum colonized the Tocantins-Araguaia basin from the Amazon basin about one million years ago. In addition, we highlighted a higher genetic diversity of O. bicirrhosum in the Amazon populations in comparison to those from the Tocantins-Araguaia basin. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.